Kaedah Pembelajaran Matematika dan Kaitannya dengan Kecerdasan Interpersonal Siswa SMA Kota Makassar - Ahmad Talib (SAINTIFIK, 2019)
This study aimed to examine the links between mathematical learning strategy and interpersonal intelligence of high school students at Makassar. The research method used is explorative and quantitative research. The population of this study is Makassar high school students, and the sample is students of class XI SMAN 8 Makassar and SMAN 22 Makassar. The data analysed by using descriptive and inferential statistics with analysis of variance (ANOVA). The results obtained were descriptions of students’ interpersonal intelligence in experimental class is in the high category, while the descriptions of students’ interpersonal intelligence in control class is in the low and middle category. The results of inferential statistical analysis shows that students’ interpersonal intelligence at Makassar high school in experimental class is better than the students’ interpersonal intelligence in control class, this means there is a link between mathematical learning strategy and interpersonal intelligence of high school students at Makassar.